Pt-based nanoparticles on non-covalent functionalized carbon nanotubes as effective electrocatalysts for proton exchange membrane fuel cells - Yan, Wei-Yong; Lu, S.; Xiang, Y.; Jiang, San Ping (Royal Society of Chemistry, 2014)
Due to their unique electronic and mechanical properties, carbon nanotubes (CNTs) have been attracting much attention as favourite catalyst supports for energy conversion and storage applications. However, CNTs require molecular engineering such as solubilization and surface modification or functionalization to tailor their surface properties for the catalyst support applications. Among various functionalization methods, non-covalent functionalization is preferred, because it enables the attachment of molecules, solvents or polyelectrolytes through π – π, CH– π or hydrophobic interactions, forming effective active sites for the uniform assembly and dispersion of Pt-based precursor and/or nanoparticles (NPs) an at the same time preserving the intrinsic electronic and structural integrity of CNTs. Non-covalent functionalization is also effective to incorporate a multi-component electrocatalyst system with significantly enhanced synergistic effects. Here, the progress in the synthesis and development of highly dispersed Pt, and Pt-based NPs such as PtRu, PtSn and PtPd on non-covalent functionalized CNTs will be presented. The significant effect of interactions between CNTs, Pt-based NPs and functionalization agents on the electrocatalytic activity of Pt-based NPs on non-covalent functionalized CNTs is discussed.